Type 2 diabetes remission rates 1‐year post‐Roux‐en‐Y gastric bypass and validation of the DiaRem score: the Ontario Bariatric Network experience. Issue 3 (28th March 2017) - Honarmand, K.; Chetty, K.; Vanniyasingam, T.; Anvari, M.; Chetty, V. T.
Summary: Roux‐en‐Y gastric bypass (RYGB) is associated with the remission of type 2 diabetes mellitus (DM). There are a number of scoring systems available that help predict type 2 diabetes remission rates after bariatric surgery; however, relatively few have been validated externally. The DiaRem score, comprised of four preoperative variables (age, haemoglobin A1c [HbA1c], sulfonylurea and insulin‐sensitizing agent use and insulin use), allows for the identification of patients who are most likely to have DM remission following RYGB. Our primary objective was to determine the variables predictive of DM remission 1 year post‐RYGB, determine how well the DiaRem score predicts DM remission 1 year post‐RYGB and identify the optimal cut‐off DiaRem score. The study is based on results of RYGB performed across multiple centres in Ontario, Canada, overseen by the Centre for Surgical Invention and Innovation in Hamilton, with direction from the Ontario Bariatric Network. Regression analysis was used to determine the predictive value of demographic and clinical variables and that of the DiaRem score. The optimal DiaRem cut‐off score was determined using sensitivity and specificity analysis. Of 3874 patients in the Ontario Bariatric Registry between January 2010 and February 2015, 915 had complete 1‐year follow‐up data. Among these, 15 were not classified as having DM at baseline and were excluded. Of the remaining 900 patients with type 2 diabetes and who underwent RYGB surgery, 333 (37.0%) had DM remission at 1‐year follow‐up. Three of four DiaRem variables (age, HbA1c, insulin use), in addition to use of any hypoglycaemic agent, were associated with DM remission. DiaRem score had moderate predictive value. A DiaRem score cut‐off of <5 had a sensitivity of 71.8% and specificity of 71.3%. This study provides guidance to clinicians in using the DiaRem score to inform the selection and prioritization of patients to ensure timely access to bariatric surgery for those who are likely to benefit the most.